2013
DOI: 10.1089/gtmb.2012.0212
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis of Two Single-Nucleotide Polymorphisms of theRELNGene with Autism in the South African Population

Abstract: Background: Autism (MIM209850) is a neurodevelopmental disorder characterized by a triad of impairments, namely impairment in social interaction, impaired communication skills, and restrictive and repetitive behavior. A number of family and twin studies have demonstrated that genetic factors play a pivotal role in the etiology of autistic disorder. Various reports of reduced levels of reelin protein in the brain and plasma in autistic patients highlighted the role of the reelin gene (RELN) in autism. There is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 64 publications
0
16
0
1
Order By: Relevance
“…Small studies have identified specific genetic risk markers and nongenetic risk factors for ASD [11, 21]. Infectious diseases such as falciparum malaria have been suggested as possible antecedents to ASD [11], but the association has not been established.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small studies have identified specific genetic risk markers and nongenetic risk factors for ASD [11, 21]. Infectious diseases such as falciparum malaria have been suggested as possible antecedents to ASD [11], but the association has not been established.…”
Section: Resultsmentioning
confidence: 99%
“…Of the six studies identified in this category, 4 explored possible genetic and biomedical factors [11, 2022]. Three of the studies looked at potential genetic markers, the ones by Ezegwui et al [20], Sharma et al [21], and Arieff et al [22]. The studies observed that certain genetic characteristics, for example, allele and genotype frequencies of 5-HTTLPR, were more likely to be associated with an increased risk of ASD.…”
Section: Resultsmentioning
confidence: 99%
“…Two papers on the genetics of ASD in SSA were identified [Arieff, Kaur, Gameeldien, van der Merwe, & Bajic, ; Sharma et al, ], both from South Africa. Arieff and colleagues compared allelic frequencies and genotypes of the 5‐HTT Linked Polymorphic Region (5‐HTTLPR) in African, mixed race, and Caucasian groups with ASD, matched controls without ASD, and an international group with ASD [Arieff et al, ].…”
Section: Genetics Of Asd In Ssamentioning
confidence: 99%
“…Allelic frequency of the South African groups differed from the Japanese, Korean, and Indian groups but not from the French, German, Israeli, Portuguese and USA groups with ASD. Sharma et al () reported significant genetic association for SNPs of the RELN gene in South African participants with a diagnosis of ASD.…”
Section: Genetics Of Asd In Ssamentioning
confidence: 99%
“…Autis merupakan gangguan perkembangan saraf secara heterogen (Corbett, 2007), yang ditandai dengan gangguan interaksi sosial (Sharma & Arieff 2013;Corbett, 2007;Al-Ayadhi 2012), komunikasi (Corbett, 2007;Al-Ayadhi 2012;Sharma & Arieff 2013), dan kebiasaan yang berulang (Iwata, 2014;Jonsson, 2014;Sharma & Arieff 2013). Gangguan tersebut terjadi dengan level yang bermacam-macam (Alabdali, 2014) dan dapat diketahui sebelum anak berumur tiga tahun (Broek et al, 2014).…”
unclassified